A szomszédos országokból Magyarországra áttelepült népesség demográfiai és gazdasági hatásai, területi mintázata - Péti Márton (Közép-európai Monográfiák, 2018)
In Western European countries, immigrants are generally in a worse position than local people. This is due to their position in society, cultural-linguistic and other differences compared to the majority society. Their qualifications and schooling differ from the host population, and the majority society is often discriminatory against them. In contrast, our research shows that Hungarian immigrants coming from outside the Hungarian borders are more qualified and educated than the Hungarian population, so they have better chances in the Hungarian labor market. This is also backed by the fact that the age structure, cultural traditions, mother tongue etc. of the immigrant population are the same as the host population so they can easily fit into society and local communities. Based on these, it can be stated that the immigrant Hungarian population coming from the neighboring countries is a major economic resource for Hungary.